BF3@K10: An Efficient Heterogeneous Montmorillonite Catalyst for the Halogenation of N-Heterocycles - El Mansouri, Az-eddine; Lachhab, Saida; Mehdi, Ahmad; Ait-Ali, Mustapha; Sanghvi, Yogesh S.; Zahouily, M.; Lazrek, Hassan B. (Synlett, 2023)
Halogenated N-heterocycles are an essential structural building block in medicinal chemistry. Herein, we describe an economical and efficient protocol for the regioselective halogenation of several N-heterocycles (pyrimidines, a pyrazole, 2-aminopyridine, theophylline, and an imidazo[1,2-a]pyridine) with BF3-doped montmorillonite (BF3@K10). The new catalyst was characterized by FTIR and 11B NMR spectroscopy, XRD, SEM, and EDS. The developed strategy provides easy and fast access to iodo-, bromo-, and chloro-N-heterocycles under mild conditions. This method was used to synthesize nine new halogenated pyrimidine derivatives. The reaction is simple and general, affording good to excellent yields of products under conventional heating or microwave conditions in the presence of BF3@K10 as an ecofriendly, inexpensive, and efficient catalyst. This protocol is clearly superior to the conventional route because it offers short reaction times, high yields, and easy workup.
Keywords: halogenation; heterogeneous catalysis; solid catalysts; montmorillonite K10; nitrogen heterocycles